Membangun Wilayah Berkelanjutan melalui Inovasi Digital dan Kepedulian Lingkungan di Kelurahan Kebalen - Iskandar, Syehan Aulia; Firdaus, Baihaqi Ahmad; AlHakim, Abdul Malik; Febrian, Muhammad Raihan; Setiaji, Tegar Aziz; Firdaus, Gading Haikal; Aska, Muhammad Febrian; Khalida, Rakhmi (Journal Of Computer Science Contributions (JUCOSCO), 2025)
Kebalen Subdistrict as a suburban area with great potential, faces various challenges in sustainable development, such as low digital literacy among MSMEs, lack of public awareness of the importance of environmental cleanliness, and a lack of green space. In an effort to overcome these challenges, the Group 07 Real Work Lecture (KKN) program is designed to support sustainable regional development through digital innovation approaches and environmental awareness. The aim of this research is to increase community digital literacy, empower local MSMEs, and encourage community participation in protecting the environment. The research method used is a participatory approach, where data is collected through direct observation, interviews and community needs surveys. The main programs carried out include training in creating web-based applications and WhatsApp Business for MSMEs, greening actions through tree planting, environmental cleanliness campaigns, and creative education for children. The analysis technique is carried out descriptively by comparing conditions before and after the activity. The research results show that the digital literacy of MSMEs has increased significantly, with 80% of participants successfully utilizing technology to manage their businesses. Greening programs and environmental cleanliness campaigns create real change by increasing public awareness of the importance of protecting the environment. Creative education has also succeeded in instilling sustainability values ​​in children. With the integration of this program, Kebalen Village shows great potential to become a more sustainable, innovative and environmentally friendly area.